Design and synthesis of novel 4-aminophenazone Schiff bases by grinding technique as prospective anti-inflammatory agents - Rashmi Arora, Rishi Sharma, Abhishek Tageza, Ajmer Singh Grewal, Balraj Saini, Sandeep Arora, Rajwinder Kaur (Journal of Applied Pharmaceutical Science, 2021)
Schiff bases are biologically diverse molecules with vast pharmacological activities and have been an area of interest in medicinal chemistry. Recently, this class also attributed new targets for drug development and research. The present study reveals the design and synthesis of the novel Schiff bases as prospective anti-inflammatory agents from the combination of 4-aminopyrazone with different aldehydes with a simple and effective grinding technique to produce different yellow-shaded products. The compounds formed were analyzed by IR spectra and 1H-nuclear magnetic resonance. Synthesized derivatives were evaluated in silico using docking studies to predict phosphodiesterase 7 (PDE7) inhibition and to investigate the binding interactions of the synthesized derivatives with active site residues of PDE7. These compounds showed appreciable binding interactions with PDE7 protein and good drug-like properties.Schiff bases are biologically diverse molecules with vast pharmacological activities and have been an area of interest in medicinal chemistry. Recently, this class also attributed new targets for drug development and research. The present study reveals the design and synthesis of the novel Schiff bases as prospective anti-inflammatory agents from the combination of 4-aminopyrazone with different aldehydes with a simple and effective grinding technique to produce different yellow-shaded products. The compounds formed were analyzed by IR spectra and 1H-nuclear magnetic resonance. Synthesized derivatives were evaluated in silico using docking studies to predict phosphodiesterase 7 (PDE7) inhibition and to investigate the binding interactions of the synthesized derivatives with active site residues of PDE7. These compounds showed appreciable binding interactions with PDE7 protein and good drug-like properties.
Keywords: 4-Aminophenazone, antiinflammatory, docking, PDE7, Schiff bases.